Marine mammal biodiversity and rare narwhal (Monodon monoceros) observations near northern Ellesmere Island, Canada. Issue 6 (8th June 2021) - Carlyle, Cody G.; Florko, Katie R. N.; Young, Brent G.; Yurkowski, David J.; Michel, Christine; Ferguson, Steven H.
Abstract: A climate‐driven decline of sea ice has increased international interest in understanding the ecology of seldom studied high‐Arctic regions projected to retain the last remnants of summer sea ice. Arctic marine mammals are vulnerable to future environmental change due to their high dependence on sea ice. We completed aerial surveys in August 2019 to document the occurrence and location of marine mammals within the recently designated Tuvaijuittuq Marine Protected Area which acts as a last refuge for ice‐associated species. We present photographic evidence of narwhals ( Monodon monoceros ), Atlantic walruses ( Odobenus rosmarus ), bearded seals ( Erignathus barbatus ), and ringed seals ( Pusa hispida ) in Archer Fjord, northern Ellesmere Island, Nunavut, Canada (81°14′–81°49′ N). We discuss these observations in the context of historical records and more recent opportunistic sightings from the region to support the hypothesis of an expansion north of the currently accepted range of narwhal. The diversity and number of observations of marine mammals in Archer Fjord is a striking contrast to the relative scarcity of the rest of the surveyed region, with very few observations of ringed seals throughout the more northerly study area. Our observations highlight opportunities to further explore high‐latitude areas that may host unique marine mammal biodiversity in the region, including narwhal.